Expert panel consensus recommendations for ambulatory blood pressure monitoring in Asia: The HOPE Asia Network - Kario, Kazuomi; Shin, Jinho; Chen, Chen Huan; Buranakitjaroen, Peera; Chia, Yook Chin; Divinagracia, Romeo; Nailes, Jennifer; Hoshide, Satoshi; Siddique, Saulat; Sison, Jorge; Soenarta, Arieska Ann; Sogunuru, Guru Prasad; et al. (Wiley, 2019)
Hypertension is an important public health issue because of its association with a number of significant diseases and adverse outcomes. However, there are important ethnic differences in the pathogenesis and cardio-/cerebrovascular consequences of hypertension. Given the large populations and rapidly aging demographic in Asian regions, optimal strategies to diagnose and manage hypertension are of high importance. Ambulatory blood pressure monitoring (ABPM) is an important out-of-office blood pressure (BP) measurement tool that should play a central role in hypertension detection and management. The use of ABPM is particularly important in Asia due to the specific features of hypertension in Asian patients, including a high prevalence of masked hypertension, disrupted BP variability with marked morning BP surge, and nocturnal hypertension. This HOPE Asia Network document summarizes region-specific literature on the relationship between ABPM parameters and cardiovascular risk and target organ damage, providing a rationale for consensus-based recommendations on the use of ABPM in Asia. The aim of these recommendations is to guide and improve clinical practice to facilitate optimal BP monitoring with the goal of optimizing patient management and expediting the efficient allocation of treatment and health care resources. This should contribute to the HOPE Asia Network mission of improving the management of hypertension and organ protection toward achieving “zero” cardiovascular events in Asia. ©2019 Wiley Periodicals, Inc.